2007
DOI: 10.1007/s11373-007-9200-4
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of zebrafish Nav1.6 sodium channel impairs embryonic locomotor activities

Abstract: Although multiple subtypes of sodium channels are expressed in most neurons, the specific contributions of the individual sodium channels remain to be studied. The role of zebrafish Na(v)1.6 sodium channels in the embryonic locomotor movements has been investigated by the antisense morpholino (MO) knockdown. MO1 and MO2 are targeted at the regions surrounding the translation start site of zebrafish Na(v)1.6 mRNA. MO3 is targeted at the RNA splicing donor site of exon 2. The correctly spliced Na(v)1.6 mRNA of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…As mentioned above, mutation of single genes can also lead to severe muscle phenotypes, so it is possible that splicing mis-regulation of only a few key targets could lead to paralysis and heart dysfunction. Proteins identified so far that are regulated by the Rbfox network include Syne1a, a Nesprin-related protein sometimes involved in pathogenesis of Emery–Dreifuss muscular dystrophy in humans (Zhang et al, 2007); Svil, a plasma membrane protein for which a muscle-specific isoform has been shown to interact with F-actin in skeletal muscle (Oh et al, 2003; Pope et al, 1998); the membrane transporters Gabrg2 and Scn8aa (Baulac et al, 2001; Chen et al, 2008); and the RNA binding protein Fxr1, which regulates somite formation in frogs (Huot et al, 2005). Interestingly, recent work showed that the completely immotile zebrafish relaxed / cacnb1 null mutant (Granato et al, 1996) is fully rescued by injection of the muscle-specific cacnb1 isoform and not other closely related isoforms (Schredelseker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, mutation of single genes can also lead to severe muscle phenotypes, so it is possible that splicing mis-regulation of only a few key targets could lead to paralysis and heart dysfunction. Proteins identified so far that are regulated by the Rbfox network include Syne1a, a Nesprin-related protein sometimes involved in pathogenesis of Emery–Dreifuss muscular dystrophy in humans (Zhang et al, 2007); Svil, a plasma membrane protein for which a muscle-specific isoform has been shown to interact with F-actin in skeletal muscle (Oh et al, 2003; Pope et al, 1998); the membrane transporters Gabrg2 and Scn8aa (Baulac et al, 2001; Chen et al, 2008); and the RNA binding protein Fxr1, which regulates somite formation in frogs (Huot et al, 2005). Interestingly, recent work showed that the completely immotile zebrafish relaxed / cacnb1 null mutant (Granato et al, 1996) is fully rescued by injection of the muscle-specific cacnb1 isoform and not other closely related isoforms (Schredelseker et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The common trace metal Cu potently disrupts olfaction in salmonids (Baldwin et al , 2003; Sandahl et al , 2004; McIntyre et al , 2008), and we have shown in a microarray study using zebrafish that Cu-olfactory impairment may be largely attributed to a transcriptional repression of conserved signal transduction genes in the zebrafish olfactory system (Tilton et al , 2008). The pesticide chlorpyrifos (CPF) is an organophosphate pesticide that alters neuronal development, synaptic stability and growth in rat and human neuronal cells (Garcia et al , 2002; Howard et al , 2005; Chen et al , 2008; Roegge et al , 2008) and is highly toxic to the fish olfactory system (Sandahl et al , 2004; Tierney et al , 2007a). In the current study, we investigated gene expression patterns underlying olfactory injury caused by exposure to CPF alone, or as a binary mixture in combination with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that such muscle malformation in D-serine-injected zebrafish embryos might result from D-serine affecting the NMDA receptors of the pre-synapse and disturbing the release of neurotransmitters from the axon terminals. Previous studies have shown that knockdown of neuronal activity led to impairment of muscle development 28 , 38 . In this regard, D-serine-induced muscle defects might be the consequences of excitotoxicity of NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous in-chorion contraction of zebrafish embryos was analyzed as previously described 28 , 29 . Briefly, zebrafish embryos at 24 hpf without or with injection of different concentrations (100, 500 and 1000 ppm) of D-serine were collected and recorded.…”
Section: Methodsmentioning
confidence: 99%